Analysis of genetic risk assessment methods - Tiešis, Vytautas; Lančinskas, Algirdas; Marcinkevičius, Virginijus (Lietuvos matematikos rinkinys, 2015)
Chronic non-communicable diseases are caused by a combination of multilocus genetic risk factors. The genetic risk assessment companies, e.g. Navigenics and 23andMe, calculate a lifetime risk of a disease by the use of strong assumptions on the total impact of the multiple SNPs genotype. The object of the paper is to compare such risk assessment methods. The theoretical disease model that describes both environmental and genetic factors has been used for evaluation of assessment methods. The system of nonlinear equations for tuning model’s parameters to real statistical parameters of the disease has been developed. The Receiver Operating Characteristic curve has been used to evaluate the quality of the methods as predictive tests.
Keywords: stochastic simulation; predictive classification; pre-symptomatic genetic risk assessment